The Appellate Body Crisis: Challenges and Reforms to the World Trade Organization Dispute Settlement Mechanism - Hameed, Meeran; Sutrisno, Nandang; Duffy, Frances Annmarie (Universitas Islam Indonesia, 2025)
The World Trade Organization’s Appellate Body—the keystone of the organization’s two-tier dispute settlement mechanism—has been immobilized since December 2019, when the United States repeatedly withheld consent for the appointment of new judges, thereby breaking the quorum required to hear appeals. This paralysis has triggered cascading operational, legal, and political consequences. Drawing on doctrinal analysis of WTO agreements and a focused case study of recent unresolved disputes, this article charts three interlinked effects of the gridlock. First, it has produced an expanding backlog of appeals and encouraged so-called “appeals into the void,” leaving panel reports in limbo and eroding legal certainty for traders and governments alike. Second, the impasse has incentivized members to experiment with ad hoc alternatives—most notably the Multi-Party Interim Appeal Arbitration Arrangement—risking fragmentation of jurisprudence and unequal access to justice across the membership. Third, the stalemate has weakened trust in the WTO’s ability to enforce multilateral rules at a moment of intensifying geopolitical rivalry, undermining incentives for future rule-making on issues such as digital trade and climate-related measures. This study argues that narrowly framed procedural fixes are insufficient; instead, a holistic reform package is required. Recommended measures include a time-bound and automatic judge-appointment process insulated from single-member vetoes, streamlined appellate procedures to curb excessive litigation delays, and a renewed political compact—possibly codified in a ministerial declaration—reaffirming shared commitments to an independent and binding dispute settlement system. Restoring a credible and predictable appellate function is indispensable for preserving the WTO’s centrality in global trade governance and for sustaining confidence in a rules-based international trading order